Элемент электронного учебника по дисциплине «Основы экологии». Программа для расчета нормативных значений - Березуцкая, Н. Л.; Дзюндзюк, Б. В.; Денисенко, Н. В. (УАДО, 2004)
There was suggested an automatically computing method of the maximal permitted level of come-out into the atmosphere and the conditions of ditch waters going into a water object. The brunch of usage: as student’s individual work and as a part of electronic coursebook «The Basics of Ecology».
Keywords: электронны учебник; основы экологии